THE INFERIORITY FEELING OF VINCENT SINCLAIR IN HOUSE OF WAX: AN INDIVIDUAL PSYCHOLOGICAL APPROACH - SUTAMININGSIH, BAYU EKA (2007)
The problem of this study in the inferiority feeling of Vincent Sinclair in House of Wax. There are two objectives of the study. The first, the writer analyzes the structural elements of the film. The second objective is to analyze the major character of the movie based the individual psychological approach. This study belongs to qualitative study. In this method, the writer uses two data sources; they are primary and secondary data sources. The primary data source and the object of the study are the film, House of Wax itself, meanwhile the secondary one is any book of literature related to this study. The writer collects the data from both primary and secondary data sources in a sort of document evidence. A result of the data shows the following conclusion, first, Vincent Sinclair wants to make the museum of wax, to fill his mother ambition and make her proud of him. While, the second Vincent wants to take revenge for his family that is ostracized by their neighborhood. In this film, Vincent becomes inferior about all the people in his social interest that he just wants to have a happy family and he wants to be a famous sculptor.